Annealing effect on the photoluminescence characteristics of ZnO-nanowires and the improved optoelectronic characteristics of p-NiO/n-ZnO nanowire UV detectors. (24th April 2015) - Li, Yu-Ren; Wan, Chung-Yun; Chang, Chia-Tsung; Huang, Yu-Chin; Tsai, Wan-Lin; Chou, Chia-Hsin; Wang, Kuang-Yu; Cheng, Huang-Chung
Abstract: Transparent ultraviolet (UV) detectors with nanoheterojunctions (NHJs) of p-type NiO and n-type ZnO nanowires (ZnO-NWs) were successfully fabricated using a DC sputtering system and a hydrothermal process, respectively. After annealing in nitrogen ambient, the near-band-edge emission to deep level emission ratio (NBE/DLE) of ZnO-NWs gradually increased as the temperature increased and reached a maximum of 28.9 at a temperature setting of 500 °C. In contrast, after annealing in oxygen atmosphere, the NBE/DLE of ZnO-NWs initially increased from 1.2 to 5.9 and then decreased to 3.2. At a reverse bias of 2 V, the devices with the 500-°C-N2 -annealed ZnO-NWs exhibited better sensitivity ( J UV / J Dark = 5.65; J Visible / J Dark = 1.35) to UV light (365 nm, 0.3 mW/cm 2 ) than those with the as-grown ZnO-NWs ( J UV / J Dark = 4.98; J Visible / J Dark = 3.82) because the structural defects in ZnO-NWs were effectively eliminated after annealing in nitrogen ambient at 500 °C.